PENGUATAN ENGINEERING LITERACY SISWA MELALUI KEGIATAN PERAKITAN HYDRAULIC ROBOTIC ARM (HYDRA) DI SDN 21 SUNGAILIAT - Pratiwi, Indah Riezky; Mayang Sari, Elisa; Novitasari, Novitasari; Reza, Amril; Akbar, Ilham; Afreza, Nanda (Pusat Penelitian dan Pengabdian Kepada Masyarakat, 2024)
The lack of activities to strengthen engineering literacy implemented at the elementary school level and the dominant learning carried out using text books are the main factors in the low engineering literacy of elementary school students. This community service activity aims to strengthen the engineering literacy of elementary school students through the Hydraulic Robotic Arm (HydRA) assembly activity at SDN 21 Sungailiiat. Through this activity, it is hoped that it can increase students' knowledge and skills related to engineering literacy, which can be used and developed further to welcome the era of society 5.0. This community service activity is carried out through a series of activities, starting with an initial survey carried out at partner locations, followed by preparing activity plans and creating activity materials, up to the activity implementation stage. This activity took place for one day at SD Negeri 21 Sungailiat and was attended by 26 students of class V A. The activity of strengthening elementary school students' engineering literacy through the Hydraulic Robotic Arm (HydRA) assembly activity at SDN 21 Sungailiiat went well, as seen by the increase in knowledge and skills students related to engineering literacy.